Sociology of Law in Corruption Crimes: Case Studies in the Judicial Process in Indonesia - Pratama, Sazia Aushar Chazradj; Usman, Sunyoto; Prasetyoningsih, Nanik (Riviera Publishing, 2025)
Corruption is one of the crucial problems in Indonesia, and it has not been addressed. Corruption occurs in almost all lines and structures of government, from the executive and legislative to judiciary, from government at the central to regional levels. This research aims to examine social sanctions' regulation in eradicating corruption in Indonesia from a sociological perspective. Methodologically, this research is library research conducted using a qualitative approach. After analyzing field data using the sociology of law and the sociology of corruption, this research found that eradicating corruption through establishing social sanctions from a sociological perspective means exile or castration. Social sanctions in this context mean maximizing social structures and community institutions to control, prevent and take action. Both prevention and action are direct, for example, making them street sweepers, or indirect, but provide a long-term deterrent effect, for example, marking their identity card (KTP) with writing or a corruptor's stamp, revoking their political rights so they can no longer hold public office.